Intervensi Mengontrol Nyeri dan Ansietas Pada Pasien dengan Sindrom Koroner Akut - Luciana Kabang; Elly Nurachmah; I Made Kariasa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This literature study aims to identify complementary therapies that can be used to reduce pain and anxiety in patients with acute coronary syndrome. The research method uses literature study, articles collected through the Google Scholar, EBSCO, Science Direct, Scopus and ProQuest databases in the form of articles published in 2018-2022 using the PRISMA approach. The article search strategy uses keywords/MeSH, namely